The Effect of Providing Incentives on Employee Morale at the Service Investment Office One-Stop Integrated (DPMPTSP) Tolitoli Regency: Pengaruh Pemberian Insentif terhadap Moral Karyawan di Kantor Investasi Jasa Terpadu (DPMPTSP) Kabupaten Tolitoli - Rulyanto R. Lasid; Sahwan Sahwan (International Journal of Economic Entrepreneurship and Business Management, 2025)
This study aims to find out and analyze the Effect of Incentive on Employee Morale at the One-Stop Integrated Service Investment Office (DPMPTSP) of Tolitoli Regency. This study uses an associative research type with a quantitative approach. The population in this study is employees who are Civil Servants at the Tolitoli Regency One-Stop Integrated Services Investment Office (DPMPTSP) which totals 42 employees. The data collection technique used saturated sampling of 42 respondents. The source of data is in the form of primary data, which is data obtained by conducting research directly related to this research. The data analysis techniques used were classical assumption tests, simple linear regression, and hypothesis testing, The results of this study were a t-calculation value of 4.563 > t-table of 2.021 and a significant value level of 0.000 < 0.05, and a Determination Coefficient of 0.342 or 34.2% showed that the provision of incentives had a significant effect on the work morale of employees at the One-Stop Integrated Service Investment Office (DPMPTSP) of Tolitoli Regency.